Somatic Genomic and Transcriptomic Characterization of Primary Ovarian Serous Borderline Tumors and Low-Grade Serous Carcinomas - Stružinská, Ivana; Hájková, Nikola; Hojný, Jan; Krkavcová, Eva; Michálková, Romana; Bui, Quang Hiep; Matěj, Radoslav; Laco, Jan; Drozenová, Jana; Fabian, Pavel; Škapa, Petr; Špůrková, Zuzana; et al. (The Journal of molecular diagnostics, 2024)
Low-grade serous carcinoma (LGSC) may develop from serous borderline tumor (SBT) tissue, where the micropapillary type (mSBT) presents the highest risk for progression. The sensitivity of LGSC to standard chemotherapy is limited, so alternative therapeutic approaches, including targeted treatment, are needed. However, knowledge about the molecular landscape of LGSC and mSBT is limited. A sample set of 137 pathologically well-defined cases (LGSC, 97; mSBT, 40) was analyzed using capture DNA next-generation sequencing (727 genes) and RNA next-generation sequencing (147 genes) to show the landscape of somatic mutations, gene fusions, expression pattern, and prognostic and predictive relevance. Class 4/5 mutations in the main driver genes (KRAS, BRAF, NRAS, ERBB2, USP9X) were detected in 48% (14/29) of mSBT cases and 63% (47/75) of LGSC cases. The USP9X mutation was detected in only 17% of LGSC cases. RNA next-generation sequencing revealed gene fusions in 6 of 64 LGSC cases (9%) and 2 of 33 mSBT cases (9%), and a heterogeneous expression profile across LGSC and mSBT. No molecular characteristics were associated with greater survival. The somatic genomic and transcriptomic profiles of 35 mSBT and 85 LGSC cases are compared for the first time. Candidate oncogenic gene fusions involving BRAF, FGFR2, or NF1 as a fusion partner were identified. Molecular testing of LGSC may be used in clinical practice to reveal therapeutically significant targets.
Keywords: Cystadenocarcinoma, Serous; Humans; RNA; Proto-Oncogene Proteins B-raf; Female; mutace; nádory vaječníků; genomika; Ovarian Neoplasms; lidé; Ubiquitin Thiolesterase; azosloučeniny; protoonkogenní proteiny B-Raf; Neoplasm Grading; ženské pohlaví; stanovení celkové genové exprese; stupeň nádoru; Azo Compounds; thiolesterasa ubikvitinu; Mutation; Gene Expression Profiling; serózní cystadenokarcinom; Genomics